Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/corr.0000000000000784
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions and the Acceptance of Evidence-based Nonsurgical Interventions for Knee Osteoarthritis. A Qualitative Study

Abstract: Background In contrast to best practice guidelines for knee osteoarthritis (OA), findings from several different healthcare settings have identified that nonsurgical treatments are underused and TKA is overused. Empirical evidence and qualitative observations suggest that patients’ willingness to accept nonsurgical interventions for knee OA is low. A qualitative investigation of why patients may feel that such interventions are of little value may be an important step toward increasing their use in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
128
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 145 publications
(145 citation statements)
references
References 28 publications
7
128
2
2
Order By: Relevance
“…Some participants believed their ‘damaged’ hip structures were caused by physical activity, loading and/or an injury; many reported being told by HCPs that their ‘damage’ had been caused by ‘faulty biomechanics’ and ageing. These findings are similar to reports among people with knee osteoarthritis18 24 and LBP 25–27. The belief that structural pathology based on radiological imaging is an accurate measure of a person’s pain experience is common at a societal level and among HCPs 28 29.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Some participants believed their ‘damaged’ hip structures were caused by physical activity, loading and/or an injury; many reported being told by HCPs that their ‘damage’ had been caused by ‘faulty biomechanics’ and ageing. These findings are similar to reports among people with knee osteoarthritis18 24 and LBP 25–27. The belief that structural pathology based on radiological imaging is an accurate measure of a person’s pain experience is common at a societal level and among HCPs 28 29.…”
Section: Discussionsupporting
confidence: 85%
“…The participants attempted to limit further damage and control their pain through activity avoidance and movement modification, such as avoiding squatting movements, adopting an antalgic gait or using upper limb strength to push themselves up from a sitting position or lift themselves out of a car. Activity avoidance and modification due to fear of doing more damage has also been reported among people with persistent LBP (eg, avoiding ‘bending’ their back or pacing activities) and knee osteoarthritis (eg, avoiding/pacing activities or choosing activities believed to cause less damage, such as cycling) 18 24 32. Research has demonstrated a relationship between negative pain beliefs, greater functional disability and motor control impairments in people with LBP33 and knee arthritis,34 35 further highlighting the interplay between cognitive factors and coping responses to pain.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Knee OA is no longer seen as a "bone to bone" disease caused by "wear and tear" that requires quick (surgical) action, but as a long-term illness, that affects the whole person and needs effective management of the symptoms. Understanding the disease, its causes and consequences may enhance the patients' motivation towards exercise and therefore self-management (30).…”
Section: Discussionmentioning
confidence: 99%
“…the members of their respective society (35). A further limitation may be that choosing an answer through multiple-choice questions and the technically imposed need for choosing an answer option to progress with the survey may have led to choice bias or position bias (30).…”
Section: Discussionmentioning
confidence: 99%